A Study on Copolymer Systems of Styrene with Diethanolamine Side Group and Methyl Methacrylate - Acikses, Aslisah; Taskan, Gokce; Barim, Gamze (Hindawi Ltd, 2018)
4-Diethanolaminomethyl styrene (DEAMSt) monomer was prepared by the modification of 4-chloromethyl styrene with diethanolamine. The copolymers in different combinations (0.11, 0.19, and 0.30 by mole) of DEAMSt and methyl methacrylate (MMA) were prepared by free radical polymerization method at 60 degrees C in the presence of 1,4-dioxane and AIBN as initiator. The structures of DEAMSt and DEAMSt-MMA copolymer were characterized by FT-IR and H-1-NMR. The glass transition temperature (T-g) of the copolymers was measured by DSC. Thermal decomposition behavior of the copolymers was investigated by TGA. The average molecular weights of the copolymers were determined by GPC. The dye uptaking properties of the copolymers were investigated using bromocresol green. Then, the dielectric constant, dielectric loss factor, and conductivity of copolymers were investigated as a function of temperature and frequency. The activation energies (E-a) of the copolymers were determined by impedance analyzer.
Keywords: Monomer Reactivity Ratios; Graft-Copolymers; Dielectric-Properties; Thermal-Degradation; Conductivity; Polymerization; Relaxation; Dependence; Complexes; Cellulose